INTERFERENCE BETWEEN SALMONELLA SEROTYPES IN INTESTINAL COLONIZATION OF CHICKENS - CORRELATION WITH IN-VITRO BEHAVIOR - Iba, A. M.; Berchieri, A.; Barrow, P. A. (Elsevier B.V., 1995)
The effect of colonisation of the alimentary tract of newly hatched chicks by different Salmonella serotypes on the establishment in the gut by other Salmonella strains inoculated afterwards was assessed. Although profound inhibition of colonisation had been found previously to be genus-specific, considerable variation was found within the Salmonella genus. Some strains were found to be much more inhibitory than others and some were more easily inhibited than were others. There was not an absolute relationship between inhibitory activity and colonisation ability. No relationship was seen between inhibition and serotype or phage types within serotypes. There was no correlation between in vivo inhibition and the extent of inhibition that occurred in early stationary phase cultures in rich, undefined broth cultures.
Keywords: SALMONELLA; INTESTINAL COLONIZATION; CHICKENS